STUDI KANDUNGAN BAHAN ORGANIK SEDIMEN TERHADAP KELIMPAHAN BIVALVIA DI PERAIRAN SEMARANG BAGIAN TIMUR - Nurfakih, Asnandi; Suryono, Chrisna Adi; Sunaryo, Sunaryo (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
The condition of waters east of Semarang allegedly tainted by the many human activities such as settlements, ports, industries, fishing and bivalves are large, it will create different ecological conditions for the biota that are inside. Study of the bivalves is considered important because of its high tolerance and live it life in order to describe the environmental changes that occur in this waters. This research was conducted on October 7, 12 November and 11 December in the waters of eastern Semarang. The material on this research was substrate or sediment, and bivalves were taken using a modification dredge. The result showed that 8 species were found, there were, Anadara granosa, Anadara gubernaculum, Anadara innaequivalvis, Anadara pilula, Marcia hiantia, Placuna placenta, Paphia undulate, and Pharella javanic. The species with the highest abundance was Anadara granosa ( 301.1 Ind / ha (Station III)). Organic matter content was highest at station II, period 2, amounting to 22.56%, and lowest was at station V, period 3, amounting to 9.48%. The correlation between organic matter content of sediment with an abundance of bivalves in the waters of eastern Semarang overall was not significant.